1997
DOI: 10.1038/39343
|View full text |Cite
|
Sign up to set email alerts
|

Control of compartmental affinity boundaries by Hedgehog

Abstract: In Drosophila, each segmental primordium is subdivided into two cell populations, the anterior (A) and posterior (P) compartments by the selective activity of the transcription factor Engrailed (En) in P cells. Under En control, P cells secrete, but cannot respond to, the signalling protein Hedgehog (Hh). In contrast, and by default, A cells are programmed to respond to Hh by expressing other signalling molecules, such as Decapentaplegic (Dpp) and Wingless (Wg), which organize growth and patterning in both com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(54 citation statements)
references
References 29 publications
3
51
0
Order By: Relevance
“…1a) [78,79]. Dpp/TGFb signalling then cooperates with Engrailed and Hedgehog signalling to maintain the A/P boundary [24,[26][27][28]. Actomyosin cabling downstream of these factors has not been directly evaluated.…”
Section: Control Of Actomyosin Cable Formation/maintenance By Signallmentioning
confidence: 99%
See 3 more Smart Citations
“…1a) [78,79]. Dpp/TGFb signalling then cooperates with Engrailed and Hedgehog signalling to maintain the A/P boundary [24,[26][27][28]. Actomyosin cabling downstream of these factors has not been directly evaluated.…”
Section: Control Of Actomyosin Cable Formation/maintenance By Signallmentioning
confidence: 99%
“…Alternately, an additional signal could act redundantly with Wingless. Bidirectional signalling is necessary to implement cell sorting at the Drosophila wing disc D/V boundary (Notch/Notch) and A/P boundary (Dpp/Hh), as well as at vertebrate rhombomeres boundaries (Eph/Ephrin) [24,[26][27][28][29][30][35][36][37]. Because actomyosin accumulates asymmetrically at the interfaces of parasegmental boundary cells [50], bidirectional signalling might be involved here as well.…”
Section: Control Of Actomyosin Cable Formation/maintenance By Signallmentioning
confidence: 99%
See 2 more Smart Citations
“…Hh signaling also induces expression of en in this region, where it controls the identity of marginal bristles [31,32]. Although studies of hh function in wing patterning have focused on its role in anterior-posterior patterning and cell fate determination, recent studies have suggested that hh plays an important role in preventing cell mixing between the anterior and posterior compartments, a function originally attributed to en [33,34]. Clones of cells that lack en do not respect compartment boundaries, leading to the suggestion that en might cell-autonomously regulate adhesive properties of posterior cells, thereby preventing them from intermixing with anterior cells.…”
Section: Hedgehog and Drosophila Wing Developmentmentioning
confidence: 99%